Gross is gross and net is net: simple, right?. (28th April 2014) - Ridge, Richard; Baker, Michael; Hall, Nick; Prahl, Ralph; Saxonis, William
The identification of the correct baseline is essential for accurately estimating the gross impacts of any measure. For example, for replacement on burnout (ROB) or an addition, there are various baselines that could be used including applicable local, state and federal energy codes and standards and current practice, which is used to represent the energy use of equipment purchased on average by consumers in the market. However, some evaluators are now arguing that using current practice as the baseline for estimating gross impacts and then adjusting these savings using a net–to–gross ratio (NTGR) is a mistake since the gross savings are in many ways closer to net than gross. While the authors agree that to refer to the difference between annual energy use associated with current practice and that of the rebated measure is not purely net savings, they disagree about which solutions to recommend.